SPATIAL VARIATION OF VULNERABILITY IN GEOGRAPHIC AREAS OF NORTH LEBANON - Sahar T. Issa; Irna van der Molen; Manal R. Nader; Jon C. Lovett (European Scientific Journal, ESJ, 2014)
This paper examines the spatial variation in vulnerability between different geographical areas of the northern coastal region of Lebanon within the context of armed conflict. The study is based on the ‘vulnerability of space’ approach and will be positioned in the academic debate on vulnerability concepts. While ‘vulnerability of place’ is referred to in literature, it has not been systematically studied in the case of Lebanon. Vulnerability symbolizes the physical, economic, political, or social susceptibility of a certain population to damage that is caused by a natural or man-made disaster. Vulnerability is multidimensional, differential, and scale-dependent, and can vary according to differential exposure, sensitivity, and coping capacity. In this paper, we identify features and manifestations of vulnerability that are particularly relevant to the coastal area of north Lebanon. We argue that the variation in a community’s vulnerability is affected not only by exposure to the environmental damage caused by repeated episodes of armed conflict but also by the sensitivity and coping capacity of the communities in the coastal area of north Lebanon. The findings are based on 500 questionnaire surveys among citizens in the study area, semi-structured and in-depth interviews with various stakeholders, and secondary literature